On instabilities of stationary scalar field configurations supported by reflecting compact stars - Yan Peng (Physics Letters B, 2019)
We study instabilities of the system composed of stationary scalar fields and asymptotically flat horizonless reflecting compact stars. In the probe limit, we obtain bounds on the scalar field frequency. Below this bound, stationary hairy stars are expected to suffer from nonlinear instabilities under massless field perturbations. In other words, we prove that stationary scalar hairy stars are unstable for scalar fields with small frequency.